2023
DOI: 10.1088/1755-1315/1130/1/012012
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on Recycled Aggregate Concrete With Partial Replacement of Cement With Flyash and Alccofine

Abstract: Recycled aggregates are the aggregates which are collected from the construction and demolition waste. Now a day the demolition waste production is more, due to this the environment gets polluted. So the use of recycled aggregates in the place of natural aggregates will decrease the waste accumulation. The scope of using recycled aggregates increasing day by day because of that the cost will decrease effectively. The main focus of this paper is to find the strength qualities of recycled aggregates so as to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…But when we check the chemical composition and chemical characteristics of fly ash, it is clear that it has some cementing property. So, it can be used as a cementing material in concrete [4]. Through this study, we can examine the differences between ordinary concrete mix and rubberized concrete mix in terms of various strengths.…”
Section: Introductionmentioning
confidence: 99%
“…But when we check the chemical composition and chemical characteristics of fly ash, it is clear that it has some cementing property. So, it can be used as a cementing material in concrete [4]. Through this study, we can examine the differences between ordinary concrete mix and rubberized concrete mix in terms of various strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Reactivating cement involves using leftover or waste cement in new construction projects instead of producing new cement from raw materials, thereby reducing the construction industry's carbon footprint, conserving natural resources, and minimising waste [10], [11]. There are several options for recycling cement and concrete, including using them as aggregates [12], [13] in new concrete production, using them as binders [9], [14], [15], and using them as raw materials in the production of blended cement [16]- [19].…”
Section: Introductionmentioning
confidence: 99%
“…The research showed that concrete consisting of a mixture of two types shows mechanical, physical, and geometric properties and a decrease in the modulus of elasticity and compressive strength similar to recycled aggregate. CH Karthik and A Nagaraju [32] with adopting a fly ash and alccofine, this paper's primary goal is to determine the strength characteristics of recycled aggregates' in order to utilize them as a sort of substitute for natural aggregates. Madhu, K. A., et al [33] with three cycles of demolition waste aggregate and 25%, 50%, 100% percentages as coarse aggregate and to achieve long sustainability, the research concentrated on the use of concrete demolition waste.…”
Section: Introductionmentioning
confidence: 99%